Looking outside education: Expanding our thinking about moving research into practice - Schneider, Jack (Education Policy Analysis Archives, 2015)
This essay explores the usefulness of looking outside of education for inspiration, particularly with regard to seemingly intractable issues that have been resigned to the margins. First, it proposes that, rather than comparing education to medicine and law—the traditional comparison fields for education—we turn instead to the “helping fields” of nursing and social work, which seem to offer better parallels. Then it considers a test case: the stalled conversation around linking research and practice in education. Finally, the work offers a model framework of the sort that might be generated through such cross-field analysis—one for organizing our thinking about what matters in moving research into practice in education.